Peningkatan Pemahaman Bacaan Peserta Didik melalui Pendekatan Berbasis Budaya (Culturally Responsive Teaching) pada Pembelajaran Bahasa Indonesia Kelas V SDN 29 Cakranegara - Amalia, Fitriana; Musaddat, Syaiful; Lestari, Eka Indah (Mataram University, 2025)
This study is a Classroom Action Research (CAR) conducted in two cycles. The purpose of this research is to improve the reading comprehension of fifth-grade students through the implementation of the Culturally Responsive Teaching (CRT) approach in Indonesian language lessons at SD Negeri 29 Cakranegara. The research subjects were 25 fifth-grade students, consisting of 18 females and 7 males. The object of the research focused on students’ engagement in understanding traditional Sasak stories. The research instruments included observation sheets to record students’ classroom activities and written tests to measure their cognitive ability in reading comprehension. Data analysis was conducted to determine the improvement in learning outcomes across cycles. The results showed that the application of the Culturally Responsive Teaching (CRT) approach effectively improved students’ learning outcomes. In the first cycle, 12 students achieved mastery while 13 students did not, resulting in a mastery percentage of 48%. In the second cycle, there was an improvement with 21 students achieving mastery and 4 students not yet achieving it, bringing the mastery percentage to 84%. Therefore, the implementation of the Culturally Responsive Teaching (CRT) approach proved effective in enhancing the reading comprehension of fifth-grade students in Indonesian language learning.